Muscle Biodynamics and Statistical Analysis - Gulmira, Yuldasheva; Bakievna, Akbarova Barchinoy; kizi, Askarova Sarvinoz Kahramonjon; o’g’li, Raxmonberdiyev Olimjon Oxunjon (American Journal of Biodiversity, 2025)
The modern system of athletes’ training is a complex multifactorial process that gradually ensures that athletes achieve the highest results. Undoubtedly, one of the most important factors in achieving sports results at the international level is not only the modern way of playing sports, but also the innate predisposition of the athlete. One of the important characteristics affecting the level of athletic performance is the composition of skeletal muscle fibers. One of the main functions of muscles is the conversion of chemical energy into mechanical work or force. When a muscle is excited, its mechanical state changes, and this change is called muscle contraction.